Una Mirada a la Web de los Datos. Caso de Estudio: Consumo de Servicios CKAN - Herrera-Cubides, Jhon Francined; Gaona-García, Paulo Alonso; Gordillo-Orjuela, Kevin (Ingeniería, 2017)
Context: In order to assess basic criteria so as to obtain preliminary guidelines on the current state of the Web of Data, we analyze the connection and use of the services offered by CKAN - Comprehensive Knowledge Archive Network; the analysis is conducted through exploration and connection to datasets published in the datahub.io open data repository. Method: We use the services offered by CKAN for browsing and downloading datasets published in Datahub.io, we propose a procedure carried out to analyze the downloaded data. The proposal consists of three key activities: (1) review and analysis of platform, (2) Setting up and using the services provided by the API and (3) download and review of the information obtained. Results: The required services offered by the platform CKAN were configured and deployed, in order to carry out queries and downloads related to each dataset. The obtained information was processed and analyzed from the downloaded JSON, allowing a comparative preliminary analysis of the information regarding the behavior of the Web of Data. Conclusions: CKAN is a powerful tool to manage data catalogs. This tool can handle a description of the data and other relevant information, from organizations that publish to people who query such information. These queries provide information as categories of organizations, data formats and owners, the type of publication licenses, links to other data, among other which are relevant to perform an analysis of the Web data.